1990
DOI: 10.1159/000281742
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Deoxycorticosterone-Producing Benign Adrenocortical Tumor

Abstract: A case of deoxycorticosterone-producing benign adrenocortical tumor is presented. A review of the English literature revealed that this is the second case of deoxycorticosterone-producing adrenocortical adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Production of these weak mineralocorticoids at an extremely high level can induce hypermineralocorticoidism. A review of the literature shows that DOC is the pre dominant product of weak mineralocorticoid-producing tumors [7][8][9], In our patient, the plasma DOC level was also raised to twice normal. However, DOC was probably not responsible for the patient's hypertension, because its mineralocorticoid action is only about one twentieth of that of aldosterone.…”
Section: Case Reportsupporting
confidence: 46%
“…Production of these weak mineralocorticoids at an extremely high level can induce hypermineralocorticoidism. A review of the literature shows that DOC is the pre dominant product of weak mineralocorticoid-producing tumors [7][8][9], In our patient, the plasma DOC level was also raised to twice normal. However, DOC was probably not responsible for the patient's hypertension, because its mineralocorticoid action is only about one twentieth of that of aldosterone.…”
Section: Case Reportsupporting
confidence: 46%
“…The normal cortisol plasma levels despite increased concentrations of 11-deoxycortisol, could be a sign of a decreased activity of 11b-hydroxylase (CYP11B1), as described previously in adrenocortical carcinoma (Saha et al, 1990) as well as in primary aldosteronism (Jamieson et al, 1996). Alternatively, cortisol and 11-deoxycortisol may serve as substrates of aldosterone synthase (CYP11B2) (Ulick et al, 1983) (Mosso et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…Saha et al 5 recently reported an adrenal tumor patient in whom 1 lp-hydroxylase deficiency was the cause for DOC excess. Consistent with their report, the ratio of corticosterone to D O C in the right adrenal tumor (4.6) was lower than that of the right normal adrenal tissue (12.5) in the present case.…”
Section: Case Reportmentioning
confidence: 99%